Development of an automated recycling process for car battery cathodes - Wang, Yuchen (My University, 2019)
The electric vehicle becomes an alternative to fossil fuel-driven vehicles and its number has risen fast. However, the LIB's capacity is decreasing over time so that the battery recycling process has become a hot topic. Stena Metall Group initiated a project for developing a highly automated and efficient recycling process for recycling 18650 (cylindrical) batteries. This thesis aimed to build an automated pre-treatment process for battery recycling and then evaluate the time consumption for the recycling line. The priority goal was to take out the cell from the battery housing and then separate anode/cathode foils. This work presented several theoretical proposals for each procedure and proposed a principal solution for the entire process which can be used on the production scale. The pre-treatment was a mechanical process that had a limited effect on the recycling of lithium, cobalt and nickel, but it can further cooperate with the hydrometallurgical, bioleaching approaches and other chemical processes in order to recycle them. The proposed solution was according to the author’s experience and thinking during the entire project, but this solution was not verified or validated in practical. In the end, this work also proposed several battery design suggestions for simplifying the recycling process.
Keywords: battery recycling process, 18650 battery, electric vehicle, production line